Partial Differential Equations and Functional Analysis The Philippe Clément Festschrift - Koelink, Erik.; Koelink, Erik.; van Neerven, Jan M.A.M.; van Neerven, Jan M.A.M.; de Pagter, Ben.; de Pagter, Ben.; Sweers, G.H.; Sweers, G.H. (Operator Theory: Advances and Applications,, 2006)
Capturing the state of the art of the interplay between partial differential equations, functional analysis, maximal regularity, and probability theory, this volume was initiated at the Delft conference on the occasion of the retirement of Philippe Clément. It will be of interest to researchers in PDEs and functional analysis.